Impact on the institutional budget of low-complexity medical care - Cuadros Talattino, Marco Antonio (2020)
The present study analyses the impact on the National Ophthalmological Institute (INO)’s budget executed in outpatient services due to medical care for patients with low-complexity pathologies, who should be treated in the primary care centers, during the period 2010-2015. Pathologies were identified, medical consultations were quantified and the budget executed in outpatient services and low-complexity pathology was estimated. The study concludes that the impact of medical care on patients with low-complexity pathologies represents 23, 54% of the INO’s budget executed in outpatient services during the study period. This level represents a reduction of 36% in consultations for patients with high-complexity pathologies. Moreover, out of the total budget executed in low-complexity pathologies, 65% refers to general consultation (ophthalmological medicine) and 35% to refraction test (visual acuity measurement). On the other hand, it is found that the budget executed in outpatient services during this period represents 21% of the INO’s institutional budget. The estimated impact is considered important; therefore, its reduction and/or correction are recommended. JEL: I1